Retrofitting Implant Overdenture Attachments: A Clinical Report - Harel Simon, DMD1 (Journal compilation, 2003)
The remake of implant-overdenture prostheses on preexisting implants can present the clinician with a challenge, especially when the prosthetic components used initially cannot be replaced